2012
DOI: 10.5194/acp-12-7577-2012
|View full text |Cite
|
Sign up to set email alerts
|

Modeling SOA formation from the oxidation of intermediate volatility <i>n</i>-alkanes

Abstract: Abstract. The chemical mechanism leading to SOA formation and ageing is expected to be a multigenerational process, i.e. a successive formation of organic compounds with higher oxidation degree and lower vapor pressure. This process is here investigated with the explicit oxidation model GECKO-A (Generator of Explicit Chemistry and Kinetics of Organics in the Atmosphere). Gas phase oxidation schemes are generated for the C 8 -C 24 series of n-alkanes. Simulations are conducted to explore the time evolution of o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
99
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(108 citation statements)
references
References 56 publications
(86 reference statements)
9
99
0
Order By: Relevance
“…Although most previous studies have considered OPOA as OOA (Robinson et al, 2007;Shrivastava et al, 2008;Murphy and Pandis, 2009;Hodzic et al, 2010;, it has been argued (Cappa and Wilson, 2012;Aumont et al, 2012) that not all OPOA is oxidized enough to be assigned to the OOA mass fraction by factor analysis. Zhang et al (2013) suggested that if some OPOA were measured as part of HOA, the CTM bias would be reduced.…”
Section: Comparison With Factor-analysis (Me-2) Ams Datamentioning
confidence: 99%
“…Although most previous studies have considered OPOA as OOA (Robinson et al, 2007;Shrivastava et al, 2008;Murphy and Pandis, 2009;Hodzic et al, 2010;, it has been argued (Cappa and Wilson, 2012;Aumont et al, 2012) that not all OPOA is oxidized enough to be assigned to the OOA mass fraction by factor analysis. Zhang et al (2013) suggested that if some OPOA were measured as part of HOA, the CTM bias would be reduced.…”
Section: Comparison With Factor-analysis (Me-2) Ams Datamentioning
confidence: 99%
“…These latter react with atmospheric oxidants leading to increasingly functionalized products with sufficiently low volatility (Aumont et al, 2012;Jimenez et al, 2009;Kroll and Seinfeld, 2008) taking part in the formation of secondary organic aerosols (SOAs) by nucleation or condensation onto preexisting particles (Fuzzi et al, 2006;Kanakidou et al, 2005). Furthermore, numerical simulation models suggest that the secondary OVOCs are still reactive and multifunctionalized several days after emission, and they thus affect the oxidant budget as well as the formation of ozone and SOA at remote locations (Aumont et al, 2005;Madronich, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The hydroxyl radical is the main oxidant in the atmosphere and therefore controls the fate of most VOCs through oxidation cycles that lead to the formation of tropospheric O 3 (Seinfeld and Pandis, 1998) and a large number of secondary oxygenated VOCs (OVOCs; Atkinson, 2000;Goldstein and Galbally, 2007). OVOCs subsequently react with atmospheric oxidants, leading to multifunctionalized compounds of lower volatility through a multigenerational oxidation process (Kroll and Seinfeld, 2008;Jimenez et al, 2009;Aumont et al, 2012). These semi-volatile compounds take part in the formation of secondary organic aerosols (SOAs) through condensation onto preexisting particles (Kanakidou et al, 2005).…”
Section: Introductionmentioning
confidence: 99%